2020
DOI: 10.1136/vr.105603
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dog‐appeasing pheromone on canine maternal behaviour during the peripartum and neonatal periods

Abstract: BackgroundParturition and the initial postpartum period are important moments in the reproductive cycle of dogs.MethodsA study assessed the effect of ADAPTIL, a dog-appeasing pheromone, on maternal behaviour during peripartum. Bitches were continuously exposed to ADAPTIL (n=20) or placebo (n=21) in double-blinded conditions from an average of about seven days before parturition up to 21 days postpartum. Differences in maternal behaviour in relation to the treatment were evaluated by the observation of specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Then using natural products was the third option (10.3%). Recently, the benefits of using dog appeasing pheromone products (ADAPTIL ® , Ceva Santé Animale, Libourne, France) during the peripartum and neonatal periods have been studied [ 64 ], and found that bitches exposed to the pheromone displayed more attention and dedicated more time to their puppies. Such practical databased evidence may modify the choice of methods to comfort bitches around parturition in the coming years.…”
Section: Discussionmentioning
confidence: 99%
“…Then using natural products was the third option (10.3%). Recently, the benefits of using dog appeasing pheromone products (ADAPTIL ® , Ceva Santé Animale, Libourne, France) during the peripartum and neonatal periods have been studied [ 64 ], and found that bitches exposed to the pheromone displayed more attention and dedicated more time to their puppies. Such practical databased evidence may modify the choice of methods to comfort bitches around parturition in the coming years.…”
Section: Discussionmentioning
confidence: 99%
“…A blinded, placebo-controlled study of the effect of ADAPTIL ® on stress reduction in dogs subjected to a thunderstorm simulation found that while all dogs showed stress behaviours above the baseline, the fear response between thunder noises was reduced in dogs with ADAPTIL ® collars compared to placebo collars [202]. Imbibed collars have been found to reduce anxiety-related aggression more effectively than diffusers, although the duration of exposure may affect these results since collar studies often exposed animals to ADAPTIL ® for 24 h prior to the behaviour analysis [194,205]. In contrast, when dogs were only exposed to diffused ADAPTIL ® in a veterinary setting 7 min prior to examination, no reduction in stress and aggression behaviours occurred, although their duration was reduced, and the frequency of relaxed states was increased [194].…”
Section: Dog Appeasing Pheromonementioning
confidence: 99%
“…Therefore, the time elapsing between mating of the female dog and the end of weaning lasts about 120 days: altogether, this phase is complex and encompasses reproductive, metabolic, emotional and behavioral processes, often interacting among them, in turn increasing the allostatic load of the animal. This long-term period deserves scientific interest, as it represents a challenging and possibly very stressful time for the female dog [1,4]. Although many studies have focused on the specific phase of pregnancy, parturition and post-partum, to the authors' knowledge, the whole period from mating until the end of weaning has only rarely been investigated in dogs [5].…”
Section: Introductionmentioning
confidence: 99%
“…Still, today, it is not uncommon to observe disturbed behavior in periparturient female dogs, possible aggressiveness towards the newborns or even cannibalism, often accompanied by insufficient grooming or nursing of the puppies, thus impairing the successful outcome of litters. Among the diverse causes underlying these troubles, environmental factors, genetics, parity and number of the newborns in a litter were suggested [1,4,6]. Other than that, the role of the Hypothalamic-Pituitary-Adrenal axis (HPA axis) in shaping maternal behavior was presumed in sheep [8,9].…”
Section: Introductionmentioning
confidence: 99%